2009
DOI: 10.1007/s10886-009-9663-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Native Porcine Olfactory Binding Proteins

Abstract: The identification of various isoforms of olfactory binding proteins is of major importance to elucidate their involvement in detection of pheromones and other odors. Here, we report the characterization of the phosphorylation of OBP (odorant binding protein) and Von Ebner's gland protein (VEG) from the pig, Sus scrofa. After labeling with specific antibodies raised against the three types of phosphorylation (Ser, Thr, Tyr), the phosphate-modified residues were mapped by using the beta-elimination followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(46 citation statements)
references
References 16 publications
2
44
0
Order By: Relevance
“…In addition, we demonstrated recently that a dynamic mechanism involving PTM could be responsible for OBP diversity and specificity (Le Danvic et al 2009;Nagnan-Le Meillour et al 2009b). Indeed, porcine OBP can be posttranslationally modified by phosphorylation, and we suggested that this PTM could generate a diversity of OBP isoforms with specific binding properties (Nagnan-Le Meillour et al 2009b). PTM is known to regulate signalling pathways, and phosphorylation could be a mechanism of regulation of OBP specificity towards odorant ligands.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In addition, we demonstrated recently that a dynamic mechanism involving PTM could be responsible for OBP diversity and specificity (Le Danvic et al 2009;Nagnan-Le Meillour et al 2009b). Indeed, porcine OBP can be posttranslationally modified by phosphorylation, and we suggested that this PTM could generate a diversity of OBP isoforms with specific binding properties (Nagnan-Le Meillour et al 2009b). PTM is known to regulate signalling pathways, and phosphorylation could be a mechanism of regulation of OBP specificity towards odorant ligands.…”
Section: Introductionmentioning
confidence: 75%
“…Typically, samples of 500 μl in buffer A were injected, and resulting fractions were collected and extensively dialyzed against MilliQ water. OBP isoforms were identified in HPLC fractions by Western blot with anti-OBP antibodies (Nagnan-Le Meillour et al 2009b). Their identity was confirmed by peptide mapping, followed by MALDI-TOF mass spectrometry as already described Immunodetection of Phosphorylations with Specific Antibodies HPLC fractions (OBP-Pichia and OBP-CHO) and total OBP-Pichia were suspended in sample buffer, to be separated by SDS-PAGE (Nagnan-Le Meillour et al 2009a).…”
Section: Expression Of Recombinant Obp In Cho Cells (Obp-cho)mentioning
confidence: 99%
See 2 more Smart Citations
“…1 and 2. Phosphorylation of mammalian OBPs has been reported in the past (41) and suggested to be a way of modifying the binding specificity of the protein. However, the function of this modification on OBPs still remains to be experimentally shown.…”
Section: Resultsmentioning
confidence: 99%